Tasks of the Financial Safety Net in Poland - Strzelczyk, Małgorzata (Journal of Finance and Financial Law, 2016)
The following article presents the main aspects of the financial safety net in Poland. Mainly, these are the institutional aspects, but also the legal aspects. Moreover, it was included in both the information on the rights and responsibilities of individual institutions, as well as how they function. Moreover, it realizes the significance of the activities of other entities in the financial system and their interrelationships. Working separately and also together as one body, prevent future crises and combat already present, as well as take care of the stability of the system and its continuous development.